Predicting Electronic Cigarette Use Among Adults in the Philippines - Fahad Khamis Aljaberi; Johnny J Yao.jr (ACHSM, 2021)
Background: The Philippines has one of the highest cigarette smoking rates in Southeast Asia. Tobacco prevention and control efforts should not be a one-size-fits-all approach. One of the most recent and highly marketed way of cutting down smoking is the use of E-cigarettes. But its use may also have potential harmful effects which would be similar to cigarette smoking. Purpose: This study aimed to determine the factors predicting electronic cigarette use among adults in a large metropolitan area in the Philippines. Methods:The study used a descriptive-correlational multivariate research design. Adults who are at least 18 years of age, who are electronic cigarettes users, dual users (electronic cigarette and cigarette users), and non-smokers were chosen for this study. The researchers utilized a researcher- made questionnaire based on the Theory of Planned Behavior (TPB) in gathering the data. Results: Multiple regression analysis suggests that positive attitude and high perceived behavioral control significantly predict intent to use electronic cigarettes. Moreover, intent to use is a significant predictor of actual e-cigarette use.  Conclusion: People who have positive attitudes and high perceived behavioral control towards e-cigarette use are most likely to have higher intent to use e-cigarettes. Further, people who have high intent to use e-cigarettes will most likely use e-cigarettes. With reverence to the findings of this study, health managers and professionals should look into how e-cigarettes are being marketed to the public which may shape their attitude and behavior. Lastly, further studies should be conducted on other variables that may predict electronic cigarette use and measure health outcomes.